Accommodating stormwater storage structure in the veranda of shop building - Yau Seng, Mah; Norazlina, Bateni; Rosmina, Ahmad Bustami; Jethro, Anak Henry Adam; Afdal Haziq, Mohammad Salehe (Accent Journals, 2021)
This paper describes the investigation to place water storage structure under the veranda of a shop building. A veranda is a commercial building feature in Southeast Asia with a narrow walkway about 3 m wide. Given the small space’s limited capability to hold rainwater from the building roof, a draining tank is, therefore, a more viable choice. Rainwaters flow in and out the tank simultaneously with an outlet control that enables water storage within. A modular-based stormwater storage system that could be assembled under the veranda was selected. Storm Water Management Model version 5.0 was used to model the system. The modular-based system's availability of field test data allowed calibration and verification exercises using the mentioned software and yielded R Square values between 0.97-0.99. As such, the parameters of the system as a storage unit were applied in the modelling of the same system in the veranda. Two cases were presented. The water storage structure was modelled in a single shop lot and a partial commercial area with six units of shop lots and surrounding streets. Modelling the single shop lot with 60% of its roof directing waters to the water storage structure was predicted to reduce 25-30% of its peak values comparing the post-development hydrographs with and without the intervention. The partial commercial area modelling yielded only 0.4-10% prediction in its reduction, suggesting additional intervention was required.